Poultry, number on farms at June 1 and at December 1 - Statistics Canada (Government of Canada, 2017)
This table contains 82 series, with data for years 1916 - 1982 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography (11 items: Canada;Newfoundland and Labrador;Prince Edward Island;Nova Scotia; ...); Survey date (2 items: At June 1;At December 1); Type of poultry (4 items: Hens and chickens;Turkeys;Geese;Ducks).